Analisis Persepsi Masyarakat terhadap Peran dan Kualitas Apoteker pada Layanan Kefarmasian di Rumah Sakit X Kota Bandung - Annisa Khalilah; Tina Rostinawati (STIKes Ibnu Sina Ajibarang, 2025)
Public perceptions regarding the role and quality of pharmacists can show how patients view the services provided and are used to evaluate the quality of services from the patient's perspective. Pharmaceutical services are currently based on patient-oriented where the relationship between pharmacists and patients greatly influences patient satisfaction, compliance with treatment plans, and the quality of health services. This study aims to analyze patient perceptions and satisfaction with pharmaceutical services provided by pharmacists and the factors that influence them at X Hospital, Bandung. The method used is non-experimental research with observational methods. Data collection was carried out by distributing questionnaire sheets to 86 respondents. The Cronbach's Alpha value on the questionnaire that used was 0.736. The data obtained shows that 84% of respondents have a positive perception of pharmacists' role, 87% have good service experience, and 100% are satisfied with the pharmaceutical services provided by pharmacists at X Hospital, Bandung City. In addition, respondents also hope that the quality of pharmaceutical services can be maintained and improved by providing patients with more in-depth medicine information, increasing pharmacists' role in dealing with routine medication consumption problems, and shortening waiting times for medicine collection.